Kelebihan dan Kekurangan Kurikulum Merdeka pada Pembelajaran Sejarah dalam Perspektif Historis - Ahmad Almarisi (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2023)
This article aims to discuss the advantages and disadvantages of the Kurikulum Merdeka in historical learning from a historical perspective. The curriculum is a design of learning material provided and taught by educators to learners through certain methods and ways with the goal of achieving national educational aspirations. The education curriculum in Indonesia often undergoes changes, this is done to perfect the previous curriculum, changes have occurred since the implementation of the Kurikulum 1947. For now, the curriculum used and developed is the Kurikulum Merdeka. In its implementation, the Kurikulum Merdeka can be applied if the school or educational unit is ready to use the Kurikulum Merdeka. If the school is not ready with the Kurikulum Merdeka system, then the school can combine the Kurikulum 2013 and the Kurikulum Merdeka. This article uses a descriptive qualitative research method with a literature study approach. The research results show that there are advantages and disadvantages of the Kurikulum Merdeka in historical learning.